The Model of Virtual Learning Approach at Mi Ma'arif Nu Limbangan - Hesti Oktaviani; Uun Fitriana Rachmah; Nadiah Qanita Rahma; Sayidin Sayidin (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
The purpose of this research is to describe the implementation of virtual learning as an implication of the progress of Science and Technology in learning at Madrasah Ibtidaiyah Ma'arif Limbangan Purbalingga Regency. Advances in science and technology bring influence in various fields, including in education. However, in the application of science and technology there are still many problems faced by teachers, including the limited facilities and the ability or experience of teachers. Whereas teachers should be able to take advantage of the progress of this science and technology in creating quality and better education. The impact of this globalization can affect learning in the future. Globalization can trigger a shift in conventional learning into modern learning. Teachers who have implemented virtual learning need to pay attention to the ways and approaches taken so that the learning is more effective and does not burden the students. The research method used is qualitative analysis. This study concludes that virtual learning in MI Ma'arif NU Limbangan Purbalingga District has two models of approaches, namely virtual learning with a psychological approach and a technological approach.